Problem based learning in dentistry ducation - Raúl Andrés Michalón Acosta; David Enmanuel Michalón Dueñas; César Gerardo Mejía Gallegos; Raúl López Fernández; Diana Eliza Palmero Urquiza; María Beatriz García Saltos (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Learning is a topic of constant discussion in the pedagogical sciences field. Within this, the student protagonism is a complex subject, which has as an alternative problem based learning. The aim of this article is to review the research supporting the effectiveness of problem based learning as a teaching method in dental education. This concept was introduced in the 1960s in Canada in response to the problems and limitations of traditional approaches to teaching. The theoretical aspects of problem based approach to learning, as well as its different trends, extrapolated to dentistry education, are presented and discussed. Problem based learning can improve dentistry students' critical thinking by teaching them to analyze and solve real problems which prepare them for their future professional life.